Conditions underpinning success in joint service-education workforce planning - Styles Laureen; Stevenson Lynn; Herringer Barbara; Purkis Mary; Van Neste-Kenny Jocelyne (BMC, 2009)
Abstract Vancouver Island lies just off the southwest coast of Canada. Separated from the large urban area of Greater Vancouver (estimated population 2.17 million) by the Georgia Strait, this geographical location poses unique challenges in delivering health care to a mixed urban, rural and remote population of approximately 730 000 people living on the main island and the surrounding Gulf Islands. These challenges are offset by opportunities for the Vancouver Island Health Authority (VIHA) to collaborate with four publicly funded post-secondary institutions in planning and implementing responses to existing and emerging health care workforce needs. In this commentary, we outline strategies we have found successful in aligning health education and training with local health needs in ways that demonstrate socially accountable outcomes. Challenges encountered through this process (i.e. regulatory reform, post-secondary policy reform, impacts of an ageing population, impact of private, for-profit educational institutions) have placed demands on us to establish and build on open and collaborative working relationships. Some of our successes can be attributed to evidence-informed decision-making. Other successes result from less tangible but no less important factors. We argue that both rational and "accidental" factors are significant - and that strategic use of "accidental" features may prove most significant in our efforts to ensure the delivery of high-quality health care to our communities.